Gravudstyr og mønter fra 1000-tallets gravpladser på Bornholm - Wagnkilde, Hanne (Hikuin, 2000)
Amulets and coins from 11th century cemeteries on Bornholm By Hanne Wagnkilde Investigations of early Christian burial sites on the island of Bornholm show that the pagan burial customs continued well into the 11th century, although they were declining. The article presents a burial site with 516 graves situated by the farm of Ndr. Grødbygård in the Åker parish. The grave goods and coins from the graves throw light on the exact time for the introduction of Christianity on the island. The grave goods mirror the gradual “amuletization” which the rich heathen equipment undergoes. Whereas the pagan Viking graves contained women with magnificent jewellery and fine clothing and wealthy men buried with weapons, wagons, and horses, the Christians islanders are just given the odd frail buckle, bead, knife, or coin. The systematic use of stereotype amulets as grave goods is a Baltic Sea phenomenon, which – in a Danish context – is only known from the early Christian graves on Bornholm. The many stereotype grave items lead one to ask whether the prayers said at the funerals went to the pagan gods or to The Almighty. This is a difficult question to answer, as the burial site has no certain traces from a church or a fence or other demarcation. However, some grave items have a cross ornament, which must reflect the faith of the deceased. The grave goods indicate the sex of the buried person, and anthropological analyses confirm the archaeological evidence of a burial place with special areas for either sex. In spite of poor preservation conditions for skeleton material, an identification of sex and age was made using skull features and teeth. The results were compared to the grave goods combination. The grave goods indicate that the population had a close contact with the pagan Slavs in Mecklenburg and Pomerania. Thus, silver beads and “Schläfenringe” (Slavic temple rings) are identical with the broken silver jewellery found in contemporary hoards. Knives with Slavic sheath mounts are also found in the graves. The relations with the Slavs is a central issue in the silver hoard research, as the hoards are often thought to have been buried as a result of raids by the Wends. However, this theory does not agree with the peaceful grave finds. The burial sites are finally fitted into a larger settlement context including the settlements of the 11th century, the hoard finds, and the structure of the contemporary society.